KOMPARASI ANALISA USAHA TANI PADI DENGAN MENGGUNAKAN PESTISIDA NABATI DAN PESTISIDA SINTETIS PADA PROGRAM IPDMIP (STUDI KASUS PETANI DI DESA SENTEBANG KECAMATAN JAWAI KABUPATEN SAMBAS) - Darma Irawan; Laila Nuzuliyah (Partner, 2022)
The purpose of this study was to determine the revenue, income and efficiency of rice farming using vegetable pesticides and synthetic pesticides of IPDMIP program in Sentebang Village, Jawai District, Sambas Regency. Determination of respondents is done by simple random sampling method. The analysis used in this study is acceptance, income and efficiency. There is a difference between the income of farming using vegetable pesticides and chemical pesticides. There is a cost efficiency in the use of botanical pesticides compared to chemical pesticides with an average difference of IDR 3,534,600,-/Ha, and an average difference of IDR 1,623,506,-/Ha. The RC data is 1,182 for vegetable pesticides and 1,340 for synthetic pesticides, so it can be interpreted that if the R/C is more than one (R/C > 1), then the farming is profitable and feasible to cultivate. Key word: Business analysis, revenue, income